2014
DOI: 10.7555/jbr.28.20120109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeic acid derivatives on polychlorinated biphenyls induced hepatotoxicity in male mice

Abstract: Chronic exposure to coplanar polychlorinated biphenyls (PCBs), a potent inducer of toxic reactive oxygen species (ROS), in the environment and food can cause liver diseases. It remains unknown whether caffeic acid derivatives (CADs) exerted protective effect on PCB-induced hepatotoxicity. We sought to evaluate the activities of 3 CADs on PCB169-induced oxidative stress and DNA damage in the liver. Male ICR mice were administered with 1 μmol/mL PCB169 at 5 mL/kg body weight for 2 weeks. The mice were given CADs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Notably, PCB exposure in mice with compromised liver worsen overall inflammation as suggested by increased levels of circulating inflammatory biomarkers [195]. To ameliorate PCB and dioxin inflammatory mechanisms, hydroxycinnamic acids [268], quercetin [78,134], EGCG [80,83,135] and resveratrol [59,269] have shown positive effects.…”
Section: Inflammation and Immunomodulationmentioning
confidence: 99%
“…Notably, PCB exposure in mice with compromised liver worsen overall inflammation as suggested by increased levels of circulating inflammatory biomarkers [195]. To ameliorate PCB and dioxin inflammatory mechanisms, hydroxycinnamic acids [268], quercetin [78,134], EGCG [80,83,135] and resveratrol [59,269] have shown positive effects.…”
Section: Inflammation and Immunomodulationmentioning
confidence: 99%
“…Moreover, growing evidence has shown that the mutation of ALDH2 involved in the oxidative pathway of alcohol metabolism can promote hepatocarcinogenesis in murine [ 30 ]. Polychlorinated biphenyls, which are potent inducers of toxic ROS, have been reported to be capable of inducing DNA damage and activating oxidative stress responses [ 31 ]. Besides the mutational events in chemical carcinogenesis, epigenetic alterations also affect the metabolism of cells and may be crucial for the development of cancer cells [ 32 , 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…148 This group also discovered that 2,3,5-trichloro-6-phenyl-[1,4]-benzoquinone and PCB169 could aggravate lipid peroxidation. 128,149 8-OHdG, the marker of oxidative DNA, was also detected in mouse hepatocytes upon PCB169 administration. 82 These DNA oxidative biomarkers were also observed in vitro upon Aroclor 1254, hydroxylated PCB, and PCB quinone challenges.…”
Section: Pcbs and Their Corresponding Metabolites Caused Oxidative St...mentioning
confidence: 96%
“…Similarly, strengthened TBARS was observed in higher concentration PCB101 exposed human lung fibroblast cells . This group also discovered that 2,3,5-trichloro-6-phenyl-[1,4]-benzoquinone and PCB169 could aggravate lipid peroxidation. , 8-OHdG, the marker of oxidative DNA, was also detected in mouse hepatocytes upon PCB169 administration . These DNA oxidative biomarkers were also observed in vitro upon Aroclor 1254, hydroxylated PCB, and PCB quinone challenges. , Unfortunately, the evidence of direct comparison of parent and daughter metabolites on the inducing of oxidative stress is limited …”
Section: Pcbs and Their Corresponding Metabolites Caused Oxidative St...mentioning
confidence: 99%